Collagen disruption as a marker for basal cell carcinoma in presurgical margin detection. Issue 9 (14th June 2018) - Rohani, Pooyan; Yaroslavsky, Anna N.; Feng, Xin; Jermain, Peter; Shaath, Tarek; Neel, Victor A.
Abstract : Introduction and Objective: Nonmelanoma skin cancers (NMSCs) are the most common malignancies in the United States. Surgery is the most common treatment for these tumors, but pre‐operative identification of surgical margins is challenging. The objective in this study was to determine whether optical polarization imaging (OPI) could be used prior to surgery to detect the extent of subclinical tumor spread by monitoring disruption in collagen. Materials and Methods: OPI is a non‐invasive and rapid imaging modality that highlights the structure of dermal collagen. OPI was used preoperatively at wavelengths of 440 and 640 nm to perform imaging of NMSCs on six patients scheduled to undergo Mohs surgery for biopsy‐proven basal cell carcinoma. This pilot study did not alter the course of routine MMS for any of the patients. The surgeon was blinded from the preoperative imaging results and completed the entire procedure without relying on the new technology. The study was conducted in an outpatient surgical setting. Patients over 18 years of age with biopsy‐proven basal cell carcinoma participated. Results and Conclusion: OPI accurately predicted the presence or absence of tumor at the surgical margin in six out of six cases, as confirmed on histology. OPI may allow efficient surgical planning by identifying tumor extension beyond visibly involved skin. Lasers Surg. Med. 50:902–907, 2018. © 2018 Wiley Periodicals, Inc.